Micropropagation of Matteucia struthiopteris (L.) Tod. through meristem proliferation from rhizomes - Zenkteler, Elżbieta (Biodiversity: Research and Conservation, 2006)
Micropropagation of Matteucia struthiopteris (L.) Tod. was undertaken to protect gene resources of the species in Poland. The main cause of low effectiveness of in vitro propagation has been the lethal browning of fern rhizome tissue after isolation. In vivo pretreatment of creeping rhizomes of ostrich fern induced their rejuvenation which was manifested by development of numerous buds. In the buds the amount of polyphenols and starch grains was decreased, as well as mitotic activity highly increased. The most effective in inducing buds break and increase of multiplication rate was Murashige Fern Multiplication Medium (MFMM) supplemented with KIN 5 mg*l-1 and NAA 0.5 mg*l-1. The regenerated microplantlets rooted best on half strength MFMM augmented with NAA 0.2 mg*l-1. In comparison with the low effectiveness of organogenesis from untreated rhizomes, their pretreatment in vivo proved to be better method to support the ostrich fern micropropagation.